Modern Prospection for Hepatic Arterial Infusion Chemotherapy in Malignancies with Liver Metastases - Yi-Hsin Liang; Yu-Yun Shao; Jia-Yi Chen; Po-Chin Liang; Ann-Lii Cheng; Zhong-Zhe Lin (International Journal of Hepatology)
Malignancy with liver metastasis plays an important role in daily oncology practice, especially for primary cancers of the gastrointestinal tract and hepatopancreatobiliary system. On account of the dual vascular supply system and the fact that most metastatic liver tumors are supplied by the hepatic artery, hepatic artery infusion chemotherapy (HAIC) is an appealing method for the treatment of liver metastases. Herein, we summarize recent study results reported in the literature regarding the use of HAIC for metastatic liver tumors, with special focus on colorectal cancer.